Characterization and pathogenicity of Bacillus pumilus isolated from trunk bulges of RRIM 3001 superclone rubber trees in Peninsular Malaysia - Mazlan, Safwan (2020)
Hevea brasiliensis (rubber tree) is well known as the tree of life for its by-products such as wood and latex. Nonetheless, the growth and performance of rubber trees are reduced substantially by bacterial species that causes trunk bulges. Trunk bulges are one of the most important diseases in rubber plantations especially in RRIM 3001 superclone. This study provides information that the causal pathogen responsible for the development of trunk bulges in rubber tree is Bacillus pumilus (B. pumilus) through isolation, identification, characterization and pathogenicity test. During October 2017 to December 2017, samples collection of infected rubber trees with trunk bulges disease was performed in four different locations with reported outbreaks. At the very first screening, all isolates were confirmed as Bacillus species by producing creamy white, filamentous and circular features on nutrient agar, and yellow pigment, circular, raised and entire form on Bacillus differentiation agar. These isolates appeared as Gram-positive rods and were positive for the catalase test. All isolates showed negative reaction for potassium hydroxide (KOH) and oxidase tests, positive for motility but negative for sulfide and indole tests. In carbohydrates fermentation, all isolates were able to utilize glucose, inositol, mannitol, sucrose, xylose and trehalose but unable to utilize lactose, maltose and arabinose. Further identification of isolates using 16S rRNA, Bsub specific gene and gyrase B gene sequence analyses disclosed that all 35 strains were clustered to the published B. pumilus from other regions worldwide. Meanwhile, phylogenetic analyses of 16S rRNA, Bsub specific gene and gyrase B gene further showed that all 35 strains were grouped with 99% bootstrap value to the published B. pumilus. By comparing phylogenetic analysis constructed from all genes tested, it showed that phylogenetic of gyrase B gene is significantly higher genetic variation compared to the 16s rRNA and Bsub specific gene. For pathogenicity study, 10 from 35 strains were chosen for this assay based on the differences in nucleotides showed in the different clades in the phylogenetic tree of Bsub specific gene. All 10 strains were virulence towards the RRIM 3001 superclone rubber tree exhibiting trunk bulges symptoms after seven days of inoculation with different degrees of virulence; weakly virulent, moderately virulent and highly virulent. Strain KD15.5 was the most virulent, while strains KD3.1 and SD12.9 were weakly virulent. Statistical results revealed relationships between their severity and geographical origins of isolates, with the most and the lowest severity were isolates from Kedah and Selangor. This study represents the first evidence on the introduction of B. pumilus associated with trunk bulges disease of rubber tree in Peninsular Malaysia. These findings provide constructive documentation on the existence of B. pumilus causing trunk bulges disease of rubber tree in Peninsular Malaysia since rubber tree has been recognized as the important commodity crop with a high economic value in this country.